MYCN and HDAC5 transcriptionally repress CD9 to trigger invasion and metastasis in neuroblastoma - Fabian, Johannes; Althoff, Kristina; Lodrini, Marco; Patil, Nitin; Abba, Mohammed L.; Thole, Theresa Maria; Schweizer, Leonille; Mechtersheimer, Gunhild; Deimling, Andreas von; Erb, Ulrike; Zöller, Margot; Allgayer, Heike; et al. (OncoTarget, 2016)
Oncotarget | https://doi.org/10.18632/oncotarget.11662 Johannes Fabian, Desirée Opitz, Kristina Althoff, Marco Lodrini, Barbara Hero, Ruth Volland, Anneleen Beckers, Katleen de Preter, Anneleen Decock, Nitin...
Gesehen am 04.07.2019